Investigations of the EPR parameters for the tetrahedral [FeX₄]- clusters in AgX (X=Cl, Br) - Song, B.-T.; Wu, S.-Y.; Kuang, M.-Q.; Zhang, Z.-H. (Condensed Matter Physics, 2012)
The EPR parameters g factors and the superhyperfine parameters for the tetrahedral [FeX₄]- clusters in AgX (X=Cl, Br) are theoretically investigated from the perturbation formulas of these parameters for a 3d⁵ ion under tetrahedra by considering both the crystal-field and charge transfer contributions.The related model parameters are quantitatively determined from the cluster approach in a uniform way. The g-shift Δg (=g-gs, where gs≈2.0023 is the spin only value) from the charge transfer contribution is opposite (positive) in sign and much larger in magnitude as compared with that from the crystal-field one. The importance of the charge transfer contribution increases rapidly with increasing the covalency and the spin-orbit coupling coefficient of the ligand and thus exhibits the order of AgCl<AgBr. The unpaired spin densities of the halogen ns, npσ and npπ orbitals are quantitatively determined from the related molecular orbital coefficients based on the cluster approach.